Analysis Of Effect Of Performance Of Public Works Department In Jepara With Balanced Scorecard Method And Regression Analysis Method - Masrurotun Masrurotun; Antonius Antonius; Rachmat Mudiyono (International Conference on Coastal and Delta Areas, 2017)
As a government agency with the largest budget utilization in the Government of Jepara, the Public Works Department of Jepara is required to demonstrate its performance optimally in meeting the needs of the community in the field of development. One of the efforts to monitor performance and maintain consistency in performing the task is performance measurement. The Balanced Scorecard (BSC) method and regression analysis method are used to design performance measurement systems to determine performance indicators appropriate to the organization's vision and mission. The purposes of this study are 1) to measure the performance of DPUD Jepara with Balanced Scorecard concept and concept of linear regression analysis with four perspective. 2) analyze the most dominant variable that affect the performance in DPUD Jepara. This study uses descriptive method with quantitative qualitative approach. Data collection is done by distributing questionnaires. The sample of study is 88 respondents. The results of study through Balance scorecard analysis with 4 perspective indicates that (1) Finance perspective include effectiveness, efficiency, and also budget transparency in good value (2) Customer prespectives include employee quantity, employee competence can reach optimum. (3) Internal business process perspective is considered good. (4) Learning and growth perspective is good because of salary conformity with work load, the existence of reward and punishment system. While through linear regression analysis showed that the four perspectives have an effect on Performance In DPUD Jepara. This result can be seen from result of ANOVA test or F test that show value of F arithmetic equal to 345.860 while value of F table equal to 2.48. The most dominant variables are finance perspective, internal business process perspective, learning & growth (infrastructure) perspectives. Keywords: Performance, Balanced Scorecard, Regression Analysis